UPAYA PENINGKATAN KOMPETENSI GURU DALAM DUNIA PENDIIDKAN - Zulhimma, Zulhimma (AIN Padangsidimpuan, 2014)
AbstractTeacher is one of the determinant efficacy of education, because a teacher has direct interaction with protege. In executing the duty, a teacher is expected to have interest, that interest is paedagogik, professional, social and personal. All sides concerned in the world of education are expected to try improving teacher interest, that is; governmental side, itself teacher and school.Keywords: Effort, Increase, Interest, Teacher and Education.